Effective Assessment of Teaching in Interdisciplinary Engineering Postgraduate Programs (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2022)
Interdisciplinary postgraduate programs have to be very effective in the engineering profession due to the explosion of knowledge in various branches. These enable engineers to effectively solve many professional problems in analyses, design, prototype development,testing, improving, mass production, marketing, and maintenance. The whole curriculum development will be based on current projects. The development of curriculum has to be from the inputs from alumni, different partner companies which are actively involved in product development, the inputs from the experts from research and development departments of theengineering universities, national research and development labs. The curricula have to be evaluated using the formative evaluation process. Then the instructional resources have to be developed based on the approved curricula and the faculty members have to be exposed to the advances in the industry, use of digital technologies, quality assurance, value engineering, manufacturing, testing, marketing, and maintenance. Then they have to prepare course plans, assignments, internships, and industry-specific dissertations. After completion of the program, the academic audit has to be undertaken for verifying the effectiveness of teaching.If there are many deficiencies, the curriculum and the instructional method have to be improved before implementation for the next batch to ensure significant benefits to the graduates. The whole process assures the development of competent graduates with adequate skills and abilities.